Conclusion and Final Thoughts. Issue 171 (May 2017) - Eagan, Kevin; McBain, Lesley; Jones, Kevin C.
Abstract : The final chapter in this issue provides a summary of the key ideas presented throughout the issue and offers recommendations for future research and practice as related to studying and serving veterans in higher education.